Letter (copy) : Senor Pascual Tomas - Citrine, Walter, 1887-1983
026-0098-001 International EAB/DB/75 9th May 1939. The Rt. Hon. Viscount Halifax, K.G., G.C.S.I., G.C.I.E., T.D., Foreign Secretary, Whitehall, S.W.1. Dear Lord Halifax, SENOR PASCUAL TOMAS. I have your letter of the 8th inst. regarding the wife and three daughters of Senor Pascual Tomas, now resident in Spain and I am very grateful indeed for the action you have taken in sending a copy of our letter to the British Consul at Valencia. I quite appreciate how difficult it is for you to intervene in such a case, particularly in view of the stringent regulations now being imposed by the Spanish National Government on Spanish nationals desiring to leave Spain. I know you will understand the reasons which prompted my approach to you and that anything at all you can do in this matter will be greatly appreciated both by myself and Senor Pascual Tomas. Yours sincerely, General Secretary. 292/946/26/98